A Syntactic Analysis on the Constituents of Noun Phrases Found in the Tale Cinderella - Suhartono, Luwandi; Simanjuntak, Hotma; Mubina, Muhammad Fathan; Viktorianus, Viktorianus; Ananta, Dio (FKIP - Universitas Tanjungpura, 2024)
This study examines English syntax, which is concerned with the study of the ordering of components or constituents in phrases and sentences. The spotlight of investigation was directed toward the ordering of the constituents of noun phrases found in the tale Cinderella. The noun phrases found in the tale were broken down into their constituent parts for two reasons. The first is to reveal the sequential ordering of constituents in noun phrases. Do all noun phrases in the tale follow the following sequential ordering: pre-modifiers + head noun + post=modifiers? Do pre-modifiers consist of determiners and adjectives? What constituents can these determinants be broken into? Do the adjectives consist of one single adjective or a series of adjectives? Do post-modifiers consist of prepositional phrases and relative clauses? How many prepositional phrases did the writer use to post-modify a head noun? How many relative clauses did the writer use to post modify the head noun? Did the writer place prepositional phrases before or after the relative clauses? Are relative clauses reduced or non-reduced in nature? Second, to reveal the types of noun phrases used by the writer of the tale